Primary and secondary supportive partnerships among HIV-positive and HIV-negative middle-aged and older gay men. - Matthew Statz; Deanna Ware; Nicholas Perry; David Huebner; Christopher Cox; Andre Brown; Steven Meanley; Sabina Haberlen; James Egan; Mark Brennan; Linda A Teplin; Robert Bolan; et al. (PLoS ONE, 2021)
This study describes the primary and secondary partnerships of aging gay men participating in the Understanding Patterns of Healthy Aging Among Men Who Have Sex with Men substudy of the Multicenter AIDS Cohort Study and examines differences in the prevalence of these relationship structures by HIV status while adjusting for age, education, and race/ethnicity. Relationships were compared within the following structural categories: "only a primary partnership", "only a secondary partnership", "both a primary and secondary relationship", or "neither a primary nor secondary relationship". There were 1,054 participants (51.9% HIV negative/48.1% HIV positive) included in the study. Participants had a median age of 62.0 years (interquartile range: 56.0-67.0) and most reported being non-Hispanic white (74.6%) and college educated (88.0%). Of the 1,004 participants with available partnership status data, 384 (38.2%) reported no primary or secondary partnerships, 108 (10.8%) reported secondary-only partnership, 385 (38.3%) reported primary-only partnership, and 127 (12.6%) reported both primary and secondary partnerships. Of participants who reported primary partnerships only, the prevalence rates (PRs) were lower among those 62 years and older, HIV positive, black non-Hispanic and Hispanics. Of participants who reported only having a secondary partnership, the PRs were higher among those 62 years and older and HIV positive. Of participants who did not report having either a primary or secondary partnership, the PRs were higher among those 62 years and older, HIV positive, and black non-Hispanic compared with their respective referent groups. There was no significant difference in PRs of having both primary and secondary partnerships by age category, HIV status, race/ethnicity, and education. This study aimed to fill a knowledge gap in the literature regarding both primary and secondary supportive partnerships among aging HIV-positive and HIV-negative gay men.